PENGARUH PADAT TEBAR TERHADAP PERTUMBUHAN DAN KELULUSHIDUPAN BENIH IKAN PATIN SIAM (Pangasius hypophthalmus) PADA SISTEM AKUAPONIK - Fandi Atmajaya; Mulyadi Mulyadi; Sukendi Sukendi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
This research was conducted on April to May 2017 in the Hatchery of TIU (Technical Implementation Unit) of Aquaculture Department, Marine and Fishery Faculty, Riau University, Riau Province. The aimed of this study was to know the effect of different fish stocking density toward the growth performance and survival rate of the Siamese shark fry on the aquaponics system. The method was using the experimental method with five treatment levels and three repeating (fifteen treatment units). The treatments were 30 fries/tank of fish stocking density (P1); 40 fries/tank of fish stocking density (P2); 50 fries/tank of fish stocking density (P3); 60 fries/tank of fish stocking density (P4); and 70 fries/tank of fish stocking density (P5). The material was 750 fries of Siamese shark with the size around 5-7 cm and it was reared for 45 days long. The results shown that the best treatment was in 60 fries/tank of fishstocking density (P4) or equivalent with 240 fishes/m2, and its absolute weight growth was 4.81 gram, absolute length growth 3.62 cm, specific growth rate 3.44 %, food efficiency 86.21 %, fresh plant weight (FPW) was 30.64 gram. Treatment by using a different fish stocking density had the same survival rate for all treatmentsthat was 100%.